Contribution of Structural Incompatibility to Asymmetrical Injury Risks in Crashes Between Two Passenger Vehicles - R Anderson; G Ponte (Journal of Road Safety, 2012)
It is well known that mass ratio affects the probability of injury and death in both vehicles in two-vehicle crashes. Likewise, other evidence suggests that typical four-wheel drive (4WD) vehicles exhibit poorer than average aggressivity such that occupants of regular vehicles are more likely to be injured in a crash when it involves a 4WD. In this study, the ratio of the incidence of injury and death to drivers in two-vehicle crashes was calculated for crashes with different vehicle mass ratios. Injury ratios were calculated for crashes involving strictly two cars and again for those crashes where the heavier vehicle was a 4WD vehicle or a light truck (LT) and the lighter vehicle was a car. There is a common dependence of the injury risk ratio on vehicle mass ratio in both classes of crash, but there is an additional relative risk to the lighter vehicle driver when the heavier vehicle is a 4WD/LT. The effect is stronger for fatality ratios. Around twice as many drivers are killed per crash in car-to-4WD/LT crashes, indicating that the increased risk to the driver of the car is not completely offset by reduced risks to the driver of the 4WD/LT.